Proceso de comercialización en la Planta Purificadora y Envasadora de Agua “La Catalina” de la ciudad de Ventanas provincia de Los Ríos periodo 2023. - De Luca León, Yadira Jacqueline (2024)
The case study titled marketing process at the “La Catalina” water purifying and bottling plant presented a deficiency in its marketing processes, mainly due to inadequate planning of the route management system and inefficient distribution logistics, which hinders timely deliveries. Additionally, failure to meet promised delivery times and the combination of delays and low-quality shipments have led to decreased sales. The dissatisfaction and mistrust generated by delays and poor quality of shipments causes damage to the company's reputation, decreasing customer loyalty and increasing the likelihood that they will look for alternative suppliers. The water drums used by the company is an important issue because they are prone to breaking during transportation, storage and use, which can cause inconvenience to customers and loss of products due to spills, using analytical and synthetic research methods. where it allowed information to be collected through various sources, with the techniques used in interviews and surveys. The need to act quickly to improve customer satisfaction and market competitiveness was evident. The use of GPS technology in a distribution logistics improvement strategy is a wise decision. Shorter and cheaper routes can be found, which will reduce operating costs such as fuel consumption and wear and tear on vehicles. By implementing this strategy, a sustainable way of delivering products will be achieved while ensuring customer satisfaction and operational efficiency through improved distribution logistics.